Comment on Jeon et al. Predictive Limitations of the Geriatric Trauma Outcome Score: A Retrospective Analysis of Mortality in Elderly Patients with Multiple Traumas and Severe Traumatic Brain Injury. Diagnostics 2025, 15, 586 - Miguel Velasco; Allen Chehimi; Jenny Chen; Marie Nour Karam; Afsheen Mansoori (Diagnostics)
The authors, Jeon et al [...]